Countries’ Competitiveness as a Factor of MNCs’ Global Expansion - USHAKOV, Denis S.; KHAMZINA, Oksana I.; KARABASSOV, Rassul A.; ZAIARNAIA, Irina A.; GNEVASHEVA, Vera A. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018DO - 10.14505//jarle.v9.6(36).32, 2019)
National competitiveness is an important factor determining the directions and instruments of modern TNCs international expansion. Based on the model proposed by the author for the re-classification of national competitiveness factors used by international organizations, the study presents an attempt to determine the role of countries competitiveness in international multinationals flows, and draws conclusions regarding the directions of state foreign economic policy modernization in the dynamics of entrepreneurship trans-nationalization.